Developing a knowledge transfer and exchange strategy for a clinical trials unit - Annabelle South; Berta Terré Torras; Hannah Rush; Anna Goodman; Sharon Love (Trials)
Abstract Need for a strategic approach to knowledge transfer and exchange Late-phase clinical trials and systematic reviews find results that have the potential to improve health outcomes for people. However, there are often delays in these results influencing clinical practice. We developed a knowledge transfer and exchange strategy to support research teams, aiming to identify activities along the research process to maximise and accelerate the research impact. Our knowledge transfer and exchange strategy The strategy has five strands of activity across the life-course of our research: 1. Partnerships with external stakeholders (including patient and public involvement, charities, policymakers, healthcare professionals, professional bodies, regulators and industry) 2. Communication (including the development of research impact strategies and use of communication tools and channels) 3. Maximising the scientific value of our studies (including open access, data and sample sharing, and incorporating multi-disciplinary components within studies) 4. Strengthening capacity (including building internal and partner capacity to communicate effectively, and strengthening the capacity of external stakeholders to understand and apply our research). 5. Learning and sharing (evaluating the impact of research, sharing lessons learnt internally and externally) The strategy has helped trial teams think systematically about impact and was easy to use. Conclusions Our strategy helps researchers systematically identify activities which may improve the usefulness and uptake of their study results. While developed in a single trials unit, we think it may be of use to others.